STATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA LANCAR MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS III MIS AL- MUSTAQIM TAHUN PELAJARAN 2022-2023 - Suryani Suryani; Oskar Hutagaluh; Rona Rona (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The use of teacher strategies in improving the ability to read fluently in indonesian subjects in class III students,for example al-mustaqim tebas sub-district,academic year 2022-2023 sambas thesis,madrasah ibtidaiyah teacher education study program tarbiyah and science faculty sultan muhammad syafiuddin sambas institute of islamic religion 2023.